INSECURITY AND GIRL CHILD EDUCATION IN NORTH-EAST NIGERIA: A CASE OF CHIBOK AND DAPCHI QUAGMIRE - Gloria Samdi Puldu; Rwang Patrick Stephen (International Studies Journal)
The growth of girl child education has been greatly endangered over the years due to the wanton threats and sporadic attacks in schools by the Boko Haram sects. This act of terror to the girl child in Chibok and Dapchi has affected the zeal, passion and desire of most girls in seeking western education. The study therefore, examines how insecurity in the north-east has hindered enrollment and commitment of girls to education since 2014. The authors argued that, there is a nexus between girl child education growth, development and security. The paper recommend adequate security to all schools in the north-east as means of confidence building for parents to release their female children to school. The method of data collection used is both primary and secondary method. The paper made use of elite theory as the theoretical framework of analysis. The paper proffered solutions to the threat to the girl child and clearly stated also the role of government, stakeholders to peace in the region. The conclusion was that, for the nation to succeed in its quest and desire to educate girls from the north-east region, security must be taken seriously.